Using Multimedia Tools and Online Resources to Teach Listening - Umar; Hartono, Rudi; Wahyuni, Sri (Journal of Education Reseach and Evaluation, 2023)
The problem faced by English teachers when teaching listening was how to make all students focus on the learning material and be active, considering that not all students can focus on what is conveyed and often there were students who also busy playing cellphones. To overcome this problem, the English teacher sometimes asked students some questions to regain their learning intention. The objective of this research is to analyze the strategies in teaching listening to students and the problems found by the English teacher in teaching listening as well as how they overcome the problems. The research was conducted by using descriptive qualitative research. The subject of this research was a English teacher. The research collected the data through interview guidance and uses library research, which compiles extensive documentation on a single or a number of topics. Both original sources and secondary sources are used in this investigation. As a conclusion, this study can argue that using multimedia to teach listening suppresses some of the unnatural aspects of the more conventional ear training in EFL classrooms while also bringing about a number of potential advantages.